Pyrolysis Products Properties from Lignite - Xu, Ying; Zhang, Guojie; Chen, Lei; Ding, Xiaokuo; Zhang, Yongfa (Asian Journal of Chemistry, 2013)
Temperature-programmed pyrolysis of lignite was investigated. The aim of this research was to determine the pyrolysis product distribution and product evolution rate during low temperature pyrolysis of lignite as a function of temperature. The pyrolysis products were analyzed by capillary gas chromatography, gas chromatography-mass spectroscopy (GC-MS) and Brunauer-Emmettteller method. The pyrolysis experiments were performed under a heating rate of 10 ºC min-1 from room temperature to a final 600 ºC and kept 0.5 h at this temperature. The Hulun Bair lignite studied in this work is characterized by high content of H and O. The low rank coal of the sample influences on the low temperature pyrolysis properties. The product productivity obtained during the pyrolysis experiments show that low temperature pyrolysis process can obtain high yield of water, gas and tar.